Solid phase transformation of carbamazepine-fumaric acid cocrystal - Mohamed Asshafie, Mohamed Sharif (2013)
The study is about the solid phase transformation of carbamazepine-fumaric acid co-crystal. Pharmaceutical area is the most importance part in human live. In pharmaceutical, the solubility of the active pharmaceutical ingredients (API) is importance physical property to be studied. Co-crystal formation is an example method to improve the solubility of an API. Carbamazepine is an API which has low solubility. In this study carbamazepine and fumaric acid are used to form co-crystal in ethanol as a solvent. The objective of this research is to study the solid phase transformation of carbamazepine-fumaric acid cocrystal. Initially the solubility of the carbamazepine is measured using gravimetric and High Performance Liquid Chromatography (HPLC). Later, the co-crystal transformation study will be proceed via varying the ratio of fumaric acid to carbamazepine using slurry method. Carbamazepine and fumaric acid are characterized using Thermal Gravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR). The result shows the solubility of carbamazepine and fumaric acid increased as temperature increased. The Fourier Transform Infrared Spectroscopy (FTIR) spectrums show the main spectrum frequency (absorption region in cmˉ¹) for carbamazepine and fumaric acid. Thermo Gravimetric Analysis (TGA) analysis showed the total decomposition for carbamazepine is approximately at 250 °C and for the fumaric acid at 260 °C. As the conclusion the solubility of carbamazepine and fumaric acid has been increased as the temperature increased. Due to the time constraints and the technical failure of the equipment (High Performance Liquid Chromatography (HPLC)) during the analysis has resulted the cocrystal transformation study could not be completed.